Price of pure agricultural insurance premiums using the Elliptical Copula Approach - Handoyo, Fiyan; Riaman, Sukono (Opción, 2020)
The study aims to investigate the price of pure agricultural insurance premiums using the Elliptical Copula Approach. Data on rainfall and rice productivity have extreme values, so the assumption of normality cannot be met. The copula is used to identify relationships between variables and determine the value of agricultural insurance premiums. Based on the data used and conducted a simulation study obtained by Gaussian Copula, the Gaussian copula shows a smaller error value. In conclusion, the Gaussian copula is better in modeling dependencies. The price of pure agricultural insurance premiums using the Gaussian copula is smaller than using t-Copula.